LEGAL PRINCIPLES OF COUNTERACTING CYBERBULLYING AGAINST CHILDREN - Lesko, Nataliia; Khomyshyn, Iryna; Parpan, Uliana; Slyvka, Mariia; Tsvok, Maryana (Journal of Education Culture and Society, 2021)
Goal. The essay explores into the legal basis for combatting cyberbullying against children in the age of information technologies. The key signs of cyberbullying against children include the lack of time and geographical limits; the large scale and speed of sharing abusive information, and the unlimited audiences. Methods. To achieve this goal, an empirical study was carried out, in which 180 first-year students (aged 17 years), who study at the Educational and Scientific Institute of Law, Psychology and Innovative Education of Lviv Polytechnic National University, took part. When studying the theoretical and methodological aspects of this research problem, the following theoretical methods were employed: analysis, synthesis, generalization of data from psychological, pedagogical, scientific and methodological literature sources. Results. The phenomenon of cyberbullying against children is available in many developed countries. The research showed that children generally are well informed about the possibilities of protecting their rights in case of cyberbullying. However, the legal basis for protecting victims of cyberbullying requires the adoption of several laws. Conclusions. Most digital rights are enshrined in various UN Human Rights Resolutions that require systematization into the single codified act – The Declaration of Digital Human Rights. The need for this act is increasingly growing. In ten years, it would be difficult to think of a model democratic society. To build a legal basis in the area of e-democracy in line with international standards, it is important to adopt the laws on protection of freedom on the Internet,” and on e-democracy, which will certainly secure digital rights of children.